A liver for a kidney: Ethics of trans‐organ paired exchange. Issue 5 (25th March 2018) - Samstein, Benjamin; de Melo‐Martin, Inmaculada; Kapur, Sandip; Ratner, Lloyd; Emond, Jean
Abstract : Living donation provides important access to organ transplantation, which is the optimal therapy for patients with end‐stage liver or kidney failure. Paired exchanges have facilitated thousands of kidney transplants and enable transplantation when the donor and recipient are incompatible. However, frequently willing and otherwise healthy donors have contraindications to the donation of the organ that their recipient needs. Trans‐organ paired exchanges would enable a donor associated with a kidney recipient to donate a lobe of liver and a donor associated with a liver recipient to donate a kidney. This article explores some of the ethical concerns that trans‐organ exchange might encounter including unbalanced donor risks, the validity of informed consent, and effects on deceased organ donation. Abstract : The authors explore some ethical concerns of trans‐organ exchange involving a liver donor associated with a kidney recipient and a kidney donor associated with a liver recipient, including unbalanced donor risks, validity of informed consent, and effects on deceased organ donation.